Peranan Hukum Adat Dalam Menjaga Kelestarian Hutan Larangan Adat Kenegerian Rumbio Kecamatan Kampar Kabupaten Kampar - Taufik Asman; M. Mardhiansyah '; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
ABSTRACT One example of common law in Indonesia is common law in Kenegerian Rumbio, Kampar District, Kampar Regency, Riau Province. Kenegerian Rumbio has banned indigenous forest still maintained continuity. The forest area is listed on the Forest department is approximately 530 ha. This is research used a snowball sampling technique, subjects were selected based on recommendations person to person according to research to be interviewed. Data collection methods used in this study were in-depth interviews, observation, and study documents. The data analysis was conducted in three phases. The first phase, researchers conducted an analysis that linked the answers intrasubjek subjects with theory and concepts related to the research. The second phase, conducted antarsubjek analysis comparing data from each subject. At this stage, researchers performed the interpretation of the data so as to achieve the purpose of research. The third phase, the data collected were then analyzed using descriptive analysis. Kenegerian Rumbio customary law has two forms of customary rules in the forest preserve customary prohibition, namely: the rules of the ban and the rules of thing is allowed. The rules of prohibition are: cutting down trees without permission from the ninik mamak, burn the forest, enable divert forest land, wildlife hunting, arrogant when entering the forest, and speaking dirty in the woods. While the form of the permitted rules are: take firewood (wood that is already dead), took the fruit has matured, and conduct scientific research. If there is a breach in the case, the perpetrator will be prosecuted according to the customary laws in Kenegerian Rumbio. The perpetrator will be given sanction in accordance with the agreement of the ninik mamak in the deliberations conducted in the customary hall.   Key word: common law, banned indigenous forest, ban, allowed